Knowledge and practice of infection control of dental impressions among dental technicians in Tripoli, Libya - Sarra Ben Hamida; Zieneb Elgarboae; Mohamed Elmaroush; Narjes Fadel (Khalij-Libya Journal of Dental and Medical Research, 2023)
Background and objectives. Cross infection among prosthodontologist and dental lab technicians is very important issue, especially after several studies found that transmission of infection to dental lab technicians is mainly by contaminated impressions or by improper handling of clinical items after arrival at the Dental laboratory. Dental impressions can be cross-contaminated by patient’s saliva and blood, which then cross-infect the dental casts poured from the impressions. The present study was carried out to evaluate the knowledge and the practice of infection control of dental impressions among dental technicians in Tripoli, Libya. Methods. This study was based on questionnaire that designed to cover different aspects of cross-infection control in the dental clinic. The questionnaire consists of 10 closed end question and 3 yes, no question. Results. The response rate was 85%. The questionnaire showed that almost 32.9% of the dental technicians did not have instructions related to disinfection in the dental lab. Upon receipt of dental impressions, the majority (80.5%) reported always rinsing them with water only. Moreover, about 7.8% of the dental technicians reported never disinfecting dental impressions and about 16.9% reported that they sometimes disinfected impressions. In the labs were the disinfection applied, 12% of the dental labs used spray disinfection (without water) and also 12% of dental technicians used immersion disinfection (without water). Conclusion. The findings of this study show that practices and awareness of dental technicians regarding infection control are less than ideal, moreover there is lack of communication between dentists and dental technicians so should increase awareness and establishing educational programs for both dentists and dental technicians to decrease the risk of transmission of diseases in dental laboratories.